The effect of organizational culture and leadership styles on firm performance a cross-cultural study among Turkey, Russia and Romania - Özer, Funda (My University, 2011)
Denison Örgüt Kültürü Modeli, Transformasyonel Liderlik, Paternalistik Liderlik, Firma Performansı, Türkiye, Romanya, Rusya

Kürselleşmenin bir sonucu olarak iş dünyasının sınırları giderek kaybolmakta ve farklı kültürlerden insanlar birbirleriyle daha yakın çalışmaktadırlar. Kurucu ve liderlerin en kritik sorumluluklarından biri farklı ülkelerde kurulan örgütlerin performansını ve verimliliğini arttırmaktır. Romanya ve Rusya komünist yönetim sonrası geçiş ekonomisi sürecine girmiş ve kapılarını dış yatırımcıya açmıştır. İyi eğitimli, ucuz iş gücüne sahip olan bu iki cazip pazara yatırım yapmak konusunda Türkiye de diğer dış yatırım yapan ülkeler gibi atak davranmıştır. Bu cazip fırsatlarla beraber yabancı firmalar öngörülemeyen bir ortam ve iç ve dış tehditlerle karşılaşmaktadırlar. Bu çalışmanın amacı, günümüzün hızla küreselleşen iş dünyasında (1) aynı kurucu tarafından Türkiye, Rusya ve Romanya gibi farklı ülkelerde kurulan örgütlerin örgüt kültürü boyutlarını karşılaştırmak, (2) bu ülkelerde bulunan örgütlerde örgüt kültürünün ve liderlik tiplerinin firma performansına olan etkisini incelemektir. Bu çalışmada örgüt kültürü boyutlarını tanımlamak için Denison Örgüt Kültürü modeli kullanılmıştır. Ülkelerin kültürel yapıları gözönüne alındığında liderlik tipleri olarak transformasyonel, transaksiyonel ve paternalistik liderlik tipleri seçilmiştir. Bu çalışma aynı kurucu tarafından Türkiye, Rusya ve Romanya’da kurulan örgüt çalışanlarının örgüt kültürü algılarının anlamlı seviyede farklı olduğunu göstermiştir. Örgüt kültürü ve firma performansı arasındaki korelasyon analizlerine bakıldığında iki değişken arasında pozitif ve anlamlı seviyede ilişki olduğu görülmektedir. Türkiye ve Romanya’daki örgütlerde firma performansıyla en yüksek ilişki gösteren örgüt kültürü boyutu misyonken, Rusya’da firma performansıyla en yüksek ilişkiyi örgüt kültürünün katılım boyutu vermektedir. Diğer liderlik tiplerine oranla transformasyonel liderlik her üç ülkede de firma performansını en fazla etkileyen liderlik tipidir. Organizational Culture, Denison Organizational Culture Model, Transformational Leadership, Paternalistic Leadership, Firm Performance, Turkey, Romania, Russia ABSTRACT As a result of globalization, the borders of business world began to disappear and people from different cultures began to be in much closer relationships. Increasing the performance and effectiveness of organizations in different cultures is one of the most crucial responsibilities of managers and the founders. Romania and Russia have experienced a transformation to a market economy after the communist period and opened doors to foreign direct investment. Companies from around the world, as well as from Turkey, have heavily investmented in those countries which have well educated and cheap labor supply. Despite these attractive opportunities, foreign firms have encountered a very unpredictable environment and myriad challenges both internal and external to the firm. The aim of the study was to (1) compare dimensions of organizational culture in organizations which were created in different countries; Turkey, Russia and Romania by the same founder, (2) investigate the effect of organizational culture and leadership styles on firm performance. In this study, for defining the organizational cultural dimensions, Denison and Mishra’s (1995) Organization Culture Model was used. As leadership styles; transformational, transactional and paternalistic leadership models were selected to define the leadership styles of those countries. This study demonstrated that there are significant differences among organizations created by same founder in Turkey, Russia, and Romania on the perception of organizational culture. Correlation analysis between dimensions of organizational culture and firm performance verify that there are positive and significant relationships between the organizational culture and employee perceptions of Firm Performance. According to correlation analysis, it is observed that in Turkey and Romania mission trait has the highest correlation with dimensions of Firm Performance whereas in Russia involvement trait has highest correlation with Firm Performance. Compared to other leadership styles transformational leadership has a stronger effect on firm performance in each country.
Keywords: Liderlik; Örgüt Kültürü; Performans, İşletmelerde; Transformasyonel Liderlik